Who says? content analysis of online mainstream media reportage of COVID-19 "medical" claims made by Philippine public officials (March 2020-March 2022) - Delfin, Rommel De Mateo 2000; Fajardo, Freyzelle Kate Vinan 2000
This study analyzes the coverage by Philippine online mainstream media of public officials who made statements regarding COVID-19 "medical" claims using the Integrated Framework for Online News Quality Assurance which evaluates online news quality and assessment of the development of developed interventions to counter creation, spread and consequences of misinformation and disinformation. The study is geared toward analyzing Philippines online media's reportage of politicians' (president, spokesperson, state lawmakers, governor, mayor) COVID-19 claims and myths and determining the gap in the media 's supposed intervention in the pieces of disinformation. The researchers would look at the reportage of six prominent COVID cure claims from six politicians from varied positions in the government in the period of trhe pandemic.